Eco-tourism for Education and Marine Conservation: The Chumbe Island Coral Park in Zanzibar - Dodds, Rachel (Téoros)

(untitled) (Université du Québec à Montréal, 2012)
Communities, in particular traditional users of natural resources, are often concerned about threats to their livelihoods and destruction of their environments but do not have the awareness, skills and political power to control the development that comes from the tourism industry. Education and collaborative partnerships are one approach that can help destinations achieve more sustainable tourism. Looking at Chumbe Island, a small island located in the Indian Ocean channel off the coast of the semi-autonomous region of Zanzibar in Tanzania, this paper examines innovative education and multi-stakeholder partnerships that have helped to avoid negative environmental and social impacts on the communities who live in the area. The environmental education programs, employment and capacity building of the Chumbe Island Coral Park Project will be focused upon.